LA GEOGRAFIA POSSIBILISTA - Fabio Lando (Bollettino della Società Geografica Italiana, 2019)
Paul Vidal de la Blache strongly influenced the future of the discipline by creating a school of thought surrounding a geography with a specifically anthropocentric vision that he defined Géographie Humaine. According to Vidal, man, intended as a society endowed with intentionality, is the agent that modifies the surface of the earth, yet his action is constrained by the environment where he operates. He hypothesizes a bidirectional relationship, consisting of impulses generated by the environment and others generated by society: such impulses interact and change over time. More specifically, the environment offers some possibilities that man and society utilize according to need and capability, following free and consciously adopted decisions. The article aims at highlighting Vidal’s epistemological foundations, substantially linked to spiritualism, contingentism, and neolamarckism, as well as how these foundations rest on five fundamental concepts: civilization and milieu are an inseparable pair whose combined action originates genres de vie, whereas landscape and region are the other inseparable pair originated by the action of a specific genre de vie. It is Febvre that will define it as Possibilistic Geography, a paradigm that will identify, up until the 1960s, the whole French geography. This paradigm will be shaken by the emergence of theoretical-quantitative geography, which, owing to its nomothetic approach, will contrast its ideographic, purely descriptive approach, which is fundamentally pre-theoretic, and fixed on the description of landscape and region.